Fitur TalkBack Pada Gawai Dalam Proses Komunikasi Bagi Tunanetra di Pertuni Kota Denpasar - Putri, Putu Ema Yundari; Kamajaya, Gede; Tamim, Imron Hadi (JURNAL ILMIAH SOSIOLOGI: SOROT; Vol 5 No 1 (2025): JISSOROT, 2025)
This study aims to analyze the TalkBack feature on gadgets in the communication process for the blind in Denpasar City. The development and advancement of technology have provided various accessibility solutions for the blind, one of which is through the TalkBack feature. This feature helps the blind to communicate independently with the help of TalkBack through text-to-speech conversion. The theory used in this study is post-phenomenology developed by Don Ihde, which examines the relationship between humans and technology in four types of relations, namely embodiment relations, hermeneutic relations, alterity relations, and background relations. This study uses a qualitative method with data collection techniques through in-depth interviews, observations, and documentation of the blind at Pertuni Denpasar City. The results of the study indicate that TalkBack has become an important aspect for the blind to interact with the digital world more independently. TalkBack provides quite significant changes to the blind at Pertuni Kota Denpasar, where the features available from TalkBack can help the blind more easily in communicating and accessing information. Now, technology as an extension of the human body, in the context of TalkBack as a substitute for the blind's sense of sight so that they can enjoy more visualizations displayed around them by interpreting text into sound, continues to interact and explore the digital world through the use of TalkBack without being limited by how the technology works. This study concludes that the TalkBack feature is efficient for use by the blind and contributes to helping the mobility of the blind, with the suggestions given being to hold routine training, mentoring by volunteers, developing features that are still inadequate for reading files and images, and making socialization aimed at companions and the general public so that they can get to know communication aids for the blind. Keywords: TalkBack, communication, blind, accessibility, post-phenomenology.